Bazex Syndrome - Rodrigues Júnior, Ismael Alves (Sociedade Brasileira de Dermatologia, 2013)

(untitled)
Acrokeratosis Paraneoplastica or Bazex syndrome is a dermatologic manifestation usually associated with the diagnosis of squamous cell carcinoma of the upper aerodigestive tract. We report a case with exuberant clinical manifestations, exemplifying the typical cutaneous lesions in this rare syndrome, in a patient with squamous cell carcinoma of the esophagus.